CUESTIONES BÁSICAS DE ÉTICA EMPRESARIAL - Polo Santillán, Miguel Ángel (2009)
The article analyzes the teleological sense of the business ethics dress as an institution which moral sense meets in the relation the stakeholders. This interrelational vision allows to understand the relation that exists between the business ethics and the civic ethics, besides the moral importance of the corporate social responsibility, overcoming this way the simple one - though necessary - deontological vision of the business ethics.